International Financial Management / Third Edition - Carter Eugene E; Rodriguez M. Rita (Prentice Hall International, 1984)
Preface, Introduction, The International Financial Environment, International Transactions and the Financial Markets, International Monetary Agreements and Institutions, Money and Banking in International Markets, The Foreign Exchange Market: Nature and Relation to the Money Market, Exhange Rate and Interest Rate Determination Theories, Financing International Operations, International Cash Management: Foreign Echange and Interest Rate Risks, Financing International Trade, Financing Operations in the Multinational Enterprise, Management of Exposure to Exchange Risk in the Foreign Enterprise, Financial Control in the Multinational Enterprise, Financial Policy in the Multinational Enterprise, Investing in Foreign Operations, Measuring Returns from International Projects, Appendices, Glossary and Present Value Tables, Index..
Preface, Introduction, The International Financial Environment, International Transactions and the Financial Markets, International Monetary Agreements and Institutions, Money and Banking in International Markets, The Foreign Exchange Market: Nature and Relation to the Money Market, Exhange Rate and Interest Rate Determination Theories, Financing International Operations, International Cash Management: Foreign Echange and Interest Rate Risks, Financing International Trade, Financing Operations in the Multinational Enterprise, Management of Exposure to Exchange Risk in the Foreign Enterprise, Financial Control in the Multinational Enterprise, Financial Policy in the Multinational Enterprise, Investing in Foreign Operations, Measuring Returns from International Projects, Appendices, Glossary and Present Value Tables, Index..